2006
DOI: 10.1021/jo060439v
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Protonation Sites:  Reactive Centers in Protonated Molecules Leading to Fragmentation in Mass Spectrometry

Abstract: It is often found in mass spectrometry that when a molecule is protonated at the thermodynamically most favorable site, no fragmentation occurs, but a major reaction is observed when the proton migrates to a different position. For benzophenones, acetophenones, and dibenzyl ether, which are all preferentially protonated at the oxygen, deacylation or dealkylation was observed in the collision-induced dissociation of the protonated molecules. For para-monosubstituted benzophenones, electron-withdrawing substitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 57 publications
2
77
0
Order By: Relevance
“…Early studies showed that in dibenzyl ether, as well as in its derivatives, the oxygen atom was the thermodynamically favored site of protonation [19]. This result is in agreement with the fact that the proton affinity (PA) values of ethers (ϳ810 kJ/mol) are usually higher than those of benzenes (ϳ750 kJ/ mol) [25].…”
Section: ␣-Aromatic Heterocycle Methyl Benzyl Ethersupporting
confidence: 65%
See 3 more Smart Citations
“…Early studies showed that in dibenzyl ether, as well as in its derivatives, the oxygen atom was the thermodynamically favored site of protonation [19]. This result is in agreement with the fact that the proton affinity (PA) values of ethers (ϳ810 kJ/mol) are usually higher than those of benzenes (ϳ750 kJ/ mol) [25].…”
Section: ␣-Aromatic Heterocycle Methyl Benzyl Ethersupporting
confidence: 65%
“…The compounds selected in this study were expected to have the particular fragmentation loss of CH 2 O, which occurs when a proton migrates from the thermodynamically favored site to the key dissociative protonation site [19,23,24]. The compounds tested were selected to be representative of different kinds of molecules, including (1) ␣-aromatic heterocycle methyl benzyl ethers, and (2) substituted-benzyl benzyl ethers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The amino group is not the best protonation site for the nucleobases and the model systems, and we have to discuss how the amino group can serve as the dissociative protonation site [46] or consider alternative mechanisms for ammonia elimination. Some guidance is provided by the emerging understanding of NH 3 elimination from peptides [47].…”
Section: Site Of Protonation and Mode Of Initial Fragmentationmentioning
confidence: 99%